Experimental and numerical investigation of magneto-plasma optical properties toward measurements of opacity relevant for compact binary objects - Pidatella, Angelo; Mascali, David; Bezmalinovich, Matteo; Emma, Giulia; Mazzaglia, Maria; Mishra, Bharat; Finocchiaro, Giorgio; Galatà, Alessio; Marletta, Salvo; Mauro, Giorgio Sebastiano; Naselli, Eugenia; Santonocito, Domenico; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Electromagnetic transient known as kilonovae (KN), are among the photonic messengers released in the post-merger phase of compact binary objects, e.g., binary neutron stars, and they have been recently observed as the electromagnetic counterpart of related gravitational wave (GW) events. Detection of KN signal plays a fundamental role in the multi-messenger astronomy entering in a sophisticated GW-detecting network. KN light-curve also delivers precious information on the composition and dynamics of the neutron-rich post-merger plasma ejecta (relying on r-process nucleosynthesis yields). In this sense, studying KN becomes of great relevance for nuclear astrophysics. Because of the highly heterogeneous composition, plasma opacity has a great impact both on radiative transport and spectroscopic observation of the KN. Theoretical models attempting in encoding the opacity of this system often fail, due to the complexity of blending plethora of both light- and heavy-r nuclei transition lines, requesting for more complete atomic database. Trapped magneto-plasmas conceived in PANDORA could answer to these requests, allowing experimental in-laboratory measurements of optical properties and opacities, at plasma densities and temperatures resembling early-stage plasma ejecta conditions, shedding light on r-process metallic species abundance at the blue-KN diffusion time. A numerical study has been recently performed, supporting the choice of first physics cases to be investigated and the design of the experimental setup. In this paper, we report on the feasibility of metallic plasmas on the basis of the results from the systematic numerical survey on optical spectra computed under non-local thermodynamic equilibrium for several light-r nuclei. A first experimental attempt of reproducing ejecta plasma conditions has been performed on the operative Flexible Plasma Trap (FPT) at the INFN-LNS and here presented, together with first plasma characterization of density and temperature, via non-invasive optical emission spectroscopy. Measured parameters supported numerical simulations to explore optical properties of NLTE gaseous and metallic plasmas, in view of the near-future plasma opacity measurements through spectroscopic techniques. The novel work so far performed on these under-dense and low-temperature plasmas, opens the route for the first-time to future in-laboratory plasma opacity measurements of metallic plasma species relevant for KN light curve studies.